Letter from Ayodeji Jeje to Olagoke Olabisi, March 28, 1977 - Jeje, Ayodeji (1977)
Letter from Ayodeji Jeje to Olagoke Olabisi (1943-) about starting the World Black Researchers Association (WBRA).
Keywords: World Black Researchers Association; Jeje, Ayodeji; Olabisi, Olagoke, 1943-